Rethinking The Concept of Economic Rehabilitation of Niger Delta Youths Through The Amnesty Programme: Towards A Literature Review - Eke, Veronica; Ebi-Ikpolada, Maccarthy Maccrobert (Research Parks Publishers, 2025)
Using literature review approach, the study focused on rethinking the concept of rehabilitation of Niger Delta youths through the amnesty programme. Relying extensively on secondary sources, the paper conceptualised the penal and medical dimensions of rehabilitation, discussed types of rehabilitation for offenders or inmates, conceptualised rehabilitation as a goal or an ideology of punishment of offenders, explained criticisms against rehabilitation, and appraised Norway’s principle of normalization and rehabilitation. It also assessed the nexus between amnesty programme and human capital development in Nigeria’s Niger Delta, and the future of rehabilitation programmes. Implicit in the literature review is the fact that the amnesty programme has failed to adequately promote human capital development and empowerment of Niger Delta youths.